Utilization of Empty Fruit Bunch as Potential Adsorbent for Ammonia Nitrogen Removal in Natural Rubber Wastewater - Nasir, Nazlizan; Daud, Zawawi; Awang, Halizah; Ab Aziz, Nur Adila; Ahmad, Baharin; Ridzuan, Mohd Baharudin; Abubakar, Mahmoud Hijab; Tajarudin, Husnul Azan (International Journal of Integrated Engineering, 2018)
The objective of this study was to identify the performance of empty fruit bunch (EFB) to assess its use as potential adsorbent in treat ammonia nitrogen in natural rubber wastewater. The adsorption method was employed to investigate the effect of a number of factors, namely, adsorbent dosage, pH, shaking speed and contact time. The results revealed that the removal of ammonia nitrogen up to 79.5% from natural rubber wastewater. The adsorption efficiency of EFB fibre was maximum at 3.5 g dosage, pH 7, 150 rpm shaking speed and 120 min contact time. The results proved that EFB fiber are good alternative low cost adsorbent for the removal of ammonia nitrogen from natural rubber wastewater. The Langmuir isotherm (R2=0.9923) described ammonia nitrogen adsorption slightly better than the Freundlich isotherm (R2 = 0.9450), suggesting a monolayer adsorption behaviour of the adsorption processes.